If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 34 = 424 Reorder the terms: 34 + 6x = 424 Solving 34 + 6x = 424 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-34' to each side of the equation. 34 + -34 + 6x = 424 + -34 Combine like terms: 34 + -34 = 0 0 + 6x = 424 + -34 6x = 424 + -34 Combine like terms: 424 + -34 = 390 6x = 390 Divide each side by '6'. x = 65 Simplifying x = 65
| K+50=9k-4 | | 206=8-6(-6x+3) | | 8-(-2.5)= | | 7x^2+4xy+4y^2=57 | | 1.5x+9-4.5x=6 | | 11-2a=3a-14 | | -16=-8x-4 | | 2x+4-x=-17 | | 9x-21-5x=31 | | 11(n-2)=-11(1-n) | | 16=-8x-4 | | 6-7a-2n-8= | | 11h+6= | | ln(3)+ln(9)=x | | 0.7x+0.4=-1 | | 4(4x+2)+5=16x+13 | | 2x=4(1.50) | | 3(x-4)+3(x-2)=0 | | -9y-3=3 | | 56=8xp | | 9x+4y=172 | | 7k+3-6k=-35 | | X+2*2=3x-8 | | -5x-4y=1 | | b+20+7b=50 | | -.5+a=.625 | | 9(x-9.9)=6.3 | | X+2+x+2=3x-8 | | 2(w-3)=1-(v+4) | | 6(3)-3y=18 | | 10(v-5)+4=11(4+5v) | | e^2x-3=10 |